Godot Was Always There: Repetition and the Formation of Customary International Law - Wouter Werner (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2019)
Rules of customary law figure prominently in today's law and policy. Across policy fields, courts and policy-makers are called to interpret and apply customary law. However, it is still a bit of a mystery how rules of customary law emerge and how they can be identified in the first place. In this paper, I set out why the mystery of customary law is bound to remain unresolved. Customary law cannot be treated as a body of rules `out there', ready for application by domestic, regional or global authorities. Instead, it is part of a process of global cooperation where rules of customary law emerge and grow because they are restated. Rules of customary law only exist if they are successfully presented as already there.
urn:nbn:de:hbz:464-20190911-113357-1
Keywords: 320; repetition; customary law; expert commitee; International Law Commission; pathways; polycentric governance